Impacts of Migration on Livelihood: A case study of Sindhupalchok District - Shrestha, Madan Gopal (Rural Development Journal, 2017)
The central objective of the study was impacts of migrants on livelihoods in the study district. This study was conducted in two communities of the Sindhupalchok districts - Talamarang1 and Melamchi2 of the Melamchi Nagarpalika3. The study was based on primary and secondary data using both qualitative and quantitative information, SPSS pc+ was used to analyze the data. Findings reveal that spatial economic inequality in the studied district and its peripheral highlands is challenging; resource access and employment opportunities are the founding factors of migration, showing the linkages between migration and poverty. In the study area similar to other studies migration is cost-sensitive, poorer are short-distance migrants and richer are long distant migrants as the cost for migration for longer distance involves low costs. Migrants seek change in livelihood patterns, showing that youths are high migratory than others and the trend of female migration is increasing. However, only some are economically benefitted while others are placed in vulnerable conditions, manifesting the problem of selectivity and reverse causality. Remittances are the secondary source of income in the study area. Higher than remittances richer in personal assets and reduces the vulnerability of being poverty. Economic inequalities are seen in the community that has no relation to the remittances. Remittances directly proportional to the economic strengths, it was found that the strength has decreased the risk, seasonality, and vulnerability that has been faced by migrant workers. Both have combined effects on improving livelihood. The situation resembles the sketch diagram as explained by Frank Ellis (2003).